Consumption Emotions and Consumer Values among Turkish Consumers during the COVID-19 Pandemic - KARABIYIK YERDEN, NEVİN (Transnational Press London Ltd, 2020)
The COVID 19 pandemic created economic havoc around the world. Along with healthcare challenges, the pandemic has also been changing consumer lifestyles. It affects business structures and service delivery too. This article draws on an investigation of the effect of consumption emotions of Turkish consumers on consumer values during the COVID 19 Pandemic. A convenience sampling method was adopted in the study and a questionnaire survey was administered to collect 390 consumer cases. The results show that the consumption emotions of Turkish consumers during the COVID 19 Pandemic had a significant positive effect on consumer values. It was found that Turkish consumers were to feel anxiety, calmness and hope more often than not during the pandemic. © 2020 TRANSNATIONAL MARKETING JOURNAL
Keywords: Consumer behaviour; consumer values; consumption emotions; COVID 19